A Portrait of the Artist as a Political Dissident : the Life and Work of Aleksandar Petrovic. - Sudar, Vlastimir, 1974- (Intellect, 2013)
Aleksandar Saša Petrovic (1929-1994) was one of the most significant filmmakers to come out of Socialist Yugoslavia. He was by far the most awarded director on a national level, winning three Golden Arenas at the Yugoslav Film Festival in Pula, as well as receiving all the highest state awards. He was also acclaimed internationally, and the first Yugoslav director to win prizes at the Cannes Film Festival, in 1967, as well as Oscar nominations in 1967 and 1968. His film, I Even Met Happy Gypsies (1967), was seen by 200,000 people in Paris alone, and was extensively distributed worldwide. The a.